2007
DOI: 10.1002/mabi.200700049
|View full text |Cite
|
Sign up to set email alerts
|

EPR Study of the Interactions between Dendrimers and Peptides Involved in Alzheimer's and Prion Diseases

Abstract: Spin-probe and spin-label techniques were used to study the interactions of the Abeta 1-28 peptide involved in Alzheimer disease and the PrP 106-126 peptide suspected to be preferentially involved in spongiform encephalopathies with three different types of dendrimers. A computer-aided EPR analysis of a positively charged and a neutral spin probe was performed by comparing the pure dendrimer and peptide systems with the dendrimer-peptide ones. Also spin-labeled PAMAM dendrimers were used to test the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 24 publications
4
67
0
Order By: Relevance
“…Studies have demonstrated that dendrimers have a particular affinity for peptides of amyloid structure [30] and that various dendrimers can inhibit the in vitro fibrilization of Aβ [31][32][33][34][35] and MAP-Tau protein, [34] suggesting that dendrimers of different charge, size and structure may serve as useful agents for investigating the pathogenic nature of different proteins involved in a wide range of different diseases. Computational methods including quantum mechanical, molecular dynamics, coarse-grained and continuum approaches could be used as an adjunct to such aggregation studies.…”
mentioning
confidence: 99%
“…Studies have demonstrated that dendrimers have a particular affinity for peptides of amyloid structure [30] and that various dendrimers can inhibit the in vitro fibrilization of Aβ [31][32][33][34][35] and MAP-Tau protein, [34] suggesting that dendrimers of different charge, size and structure may serve as useful agents for investigating the pathogenic nature of different proteins involved in a wide range of different diseases. Computational methods including quantum mechanical, molecular dynamics, coarse-grained and continuum approaches could be used as an adjunct to such aggregation studies.…”
mentioning
confidence: 99%
“…Depending on the sugar on the surface and the number of molecules, we can observe the different extend of triggering apoptosis in those cells due to the diversity in affecting particular gene pathways [48][49][50][51]. Lysine dendrimers, PAMAM, PPI, and phosphorus have been reported to be able to modulate amyloid peptide aggregation in solution [52][53][54]. The deposition of amyloid fibrils is characteristic in neurological disorders as well as prion and Alzheimer's diseases.…”
Section: Dendrimers As Drug Delivery Systemsmentioning
confidence: 99%
“…Studies have shown that various dendrimers (including mPPI) can inhibit the in vitro fibrilization of Aβ 1-28 (a fragment of Aβ) and reduce the toxicity of the fibrils formed. 18,[25][26][27] In addition, phosphorous dendrimers have recently been shown to affect the aggregation of MAP-Tau protein. 27 Hyperphosphorylated tau is a major component of the neurofibrillary tangles present in Alzheimer disease, frontotemporal dementia and the tauopathies.…”
Section: Dendrimer Potential In Treatment Of Other Neurodegenerative mentioning
confidence: 99%